Pengaruh Asimetri Informasi Dan Kualitas Audit Terhadap Manajemen Laba Dengan Pengungkapan Informasi Sebagai Variabel Moderasi Pada Perusahaan Yang Termasuk Indek LQ45 Di Bursa Efek Indonesia - Sundarta, M. Imam (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
This study aimed to examine the effect of information asymmetry and audit quality on earnings manajamen with information disclosure as moderating variable. Consistent with previous studies that information asymmetry, quality audit significant effect on earnings management. Information disclosure and earnings management gives an indication of the negative correlation. Increased disclosure causes managers the flexibility to perform earnings management will less. There is a relationship of audit quality and earnings management. The hypothesis put forward whether there is a positive relationship between the information asymmetry on the earnings management, a negative relationship between the quality auditor with earnings management, negative relationship information disclosure to earnings management, information disclosure has a negative correlation relationship with information asymmetry to earnings management, the information disclosure has a positive relationship with audit quality to profit management. Results showed that the information asymmetry, quality auditors, disclosure does not significantly affect the earnings management. The relationship disclosure information to information asymmetry moderate on earnings management is not significant. The relationship information disclosure moderate of audit quality on earnings management is not significant. Keywords: information asymmetry, audit quality, earnings management, information disclosure, discretionary accruals